2016
DOI: 10.1007/s00520-016-3541-3
|View full text |Cite
|
Sign up to set email alerts
|

Associations between dyadic coping and supportive care needs: findings from a study with hematologic cancer patients and their partners

Abstract: In order to diminish SCN of patients and partners, a possible way is to strengthen the quality of the dyadic relation. Due to its associations with elevated SCN, stress communication and negative dyadic coping behaviours may be useful targets for psychosocial interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 31 publications
5
25
0
3
Order By: Relevance
“…Regarding the year of publication, 36 out of 62 articles were published in 2017 and 28 in 2018. Countries where the respective studies were conducted were the USA/Canada ( n = 23) [9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31], Scandinavia ( n = 7) [32,33,34,35,36,37,38], UK ( n = 4) [39,40,41,42], Germany ( n = 4) [43,44,45,46], Southern Europe (Italy, Portugal, Spain; n = 8) [47,48,49,50,51,52,53,54], East Asia (Japan, China, Korea, Taiwan; n = 4) [55,56,57,58,59,60], Australia/New Zealand ( n = 4) [61,62,63,64], other ( n = 4) [65,66,67,68], and multinational ( n = 2) [69,70].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the year of publication, 36 out of 62 articles were published in 2017 and 28 in 2018. Countries where the respective studies were conducted were the USA/Canada ( n = 23) [9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31], Scandinavia ( n = 7) [32,33,34,35,36,37,38], UK ( n = 4) [39,40,41,42], Germany ( n = 4) [43,44,45,46], Southern Europe (Italy, Portugal, Spain; n = 8) [47,48,49,50,51,52,53,54], East Asia (Japan, China, Korea, Taiwan; n = 4) [55,56,57,58,59,60], Australia/New Zealand ( n = 4) [61,62,63,64], other ( n = 4) [65,66,67,68], and multinational ( n = 2) [69,70].…”
Section: Resultsmentioning
confidence: 99%
“…Forty-seven studies reported on relatives of advanced cancer patient’s [9,10,11,13,15,16,17,18,19,20,21,22,23,24,26,27,28,29,30,31,32,34,36,37,38,39,42,43,44,46,47,48,49,50,51,52,53,55,56,57,58,59,60,61,65,66,67] and 15 studies included relatives of mixed patient samples [12,14,25,33,35,40,41,45,54,62,63,64,68,69,70]. The environment in which the patient received palliative or hospice care were home care in 18 studies [10,14,25,26,27,30,3...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies with Western couples in which one partner suffers from depression (Bodenmann et al, 2004) or cancer (e.g., Weißflog et al, 2016) have indicated that patients tend to communicate about their stress less frequently than their partners do. It is possible that depressed patients might suffer from a lack of energy, generally employ maladaptive coping strategies (Kovacs and Beck, 1978), and thus experience a decline in their communication competences (Hoffmann et al, 2016), whereas patients with cancer might consciously hold back information that would make their partner worry.…”
Section: Stress Communication (Stm)mentioning
confidence: 99%
“…In German couples coping with COPD, use of hostile/ambivalent DC is related to lower quality of life (Vaske et al, 2015). German couples coping with a partner's hematologic malignancy reported higher unmet supportive care needs when hostile/ambivalent DC was higher (Weißflog et al, 2016). When coping with breast cancer, hostile/ambivalent DC was associated with partners' poorer emotional well-being and patients' poorer physical well-being in patients in American couples (Feldman and Broussard, 2006), and with depressive symptoms and lower relationship quality in Danish couples (Rottmann et al, 2015).…”
Section: Individual Negative Dc: Hostile/ambivalent DC (Stm)mentioning
confidence: 99%